First record of mixed-species heron colony: cattle egret (Bubulcus ibis), Squacco Heron (Ardeola ralloides) and Little Egret (Egretta garzetta) breeding at Famagusta Freshwater Lake in Cyprus - Charalambidou, I.; Gucel, S. (Universiti Kebangsaan Malaysia, 2013)
This study constitutes the first record of a mixed-species heron colony and of a breeding population of Squacco Heron (Ardeola ralloides) in Cyprus. The colony, located at Famagusta Freshwater Lake, was surveyed from March to June 2007. The survey were terminated after 25 June when it was not possible to boat to the colony due to decreasing water levels. The total number of active nests, i.e. containing eggs and/or hatchlings, was 135 for Cattle Egret (Bubulcus ibis); 38 for Squacco Heron and 4 for Little Egret (Egretta garzetta). Cattle Egrets started nest building and egg laying at the beginning of March and hatching started by the end of March. Egg-laying and hatching continued throughout June, possibly due to second broods. Mean clutch size was 3.5±0.8 eggs (range 1-5; n=135). Mean hatching success was 2.9±1 hatched egg per nest (range = 1-5; n=54) and mean breeding success was 2.8±1 chick per nest (range = 0-5; n=36) for chicks surviving up to 15 days after hatching. Squacco Herons started nest building and egg laying by the end of May and hatching started by mid June. Egg-laying and hatching continued throughout June and probably in July and August. As surveys were terminated in June, it was not possible to collect sufficient data on the breeding chronology of this species. Mean clutch size was 3.1 ± 0.8 egg (range 2-4; n=38), which was lower than European estimates. A multitude of activities at and around Famagusta Freshwater Lake pose potential threats to the conservation of the colony resulting in an urgent need for management of the wetland.